Strategi Pengembangan Program "Kudus Asik" dalam Mewujudkan Zero Waste melalui Pengelolaan Sampah Berkelanjutan - Setyaputri, Nanda Aji; Pangestika, Zalma Niendya; Pujiati, Amin; Melati, Inayah Sari (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Poor waste management is one of the causes of environmental pollution. The amount of waste that increases every year without optimal management results in environmental pollution. Through the “Kudus Asik” Program initiated by Bakti Lingkungan Djarum Foundation (BLDF) and in collaboration with the Office of Housing, Settlement Areas, and the Environment (PKPLH) becomes increasingly relevant following environmental problems. This activity is aimed at 370 partners who have joined the “Kudus Asik” Program consisting of restaurants, traditional markets, village communities, hotels, corporations and other sectors in Kudus Regency. The goal is to contribute to solving waste problems in order to realize sustainable waste management through an environmental care movement. The method used was a workshop activity in order to provide insight into waste processing into creative products with economic value in collaboration with Kertabumi Recycling Center. The response of the partners through these activities showed very positive enthusiasm and involvement.